2019
DOI: 10.1016/j.celrep.2018.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Factor 1 Drives Intergenic Association of Its Target Gene Loci upon Heat Shock

Abstract: Highlights d Hsf1, but not Msn2/Msn4, drives gene coalescence in response to heat shock d Hsf1-target genes coalesce, while genes interposed between them do not d Ectopic targeting of Hsf1 drives coalescence of a heterologous gene d Preventing Hsf1 binding to a natural HSP gene selectively obviates its coalescence

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 49 publications
8
37
0
Order By: Relevance
“…Confocal imaging was performed at the Nikon Imaging Center at the Whitehead Institute for Biomedical research using the Andor spinning disc system as previously described (23). Heat shock was performed on live cells using an objective heater as described (24). Hsc82 is the yeast homolog of Hsp90.…”
Section: Confocal Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Confocal imaging was performed at the Nikon Imaging Center at the Whitehead Institute for Biomedical research using the Andor spinning disc system as previously described (23). Heat shock was performed on live cells using an objective heater as described (24). Hsc82 is the yeast homolog of Hsp90.…”
Section: Confocal Imagingmentioning
confidence: 99%
“…First, the clients that titrate Hsp70 away upon heat shock are thought to be primarily nascent proteins emerging from ribosomes in the in the cytosol (15). Yet, Hsf1 activates target gene transcription in the nucleus in less than a minute following heat shock (24). How do cytosolic clients titrate away nuclear Hsp70 so quickly, especially given that the molecular ratio of Hsp70:Hsf1 in yeast cells exceeds 1000:1 (25)?…”
Section: Introductionmentioning
confidence: 99%
“…In doing so, this study goes beyond correlation and directly establishes the causal function of chromosome topology in this process. In yeast, chromosome conformation was also thought to affect transcription 17,[39][40][41][42] and DNA replication 43 . In the future, CICI can be used to study these 3D genome functions.…”
Section: Fig 2d and E)mentioning
confidence: 99%
“…In addition, proteins that set up chromosome interactions may also directly participate in genomic processes. For example, the looping between the Locus Control Region (LCR) enhancer and the β -globin promoter is established by transcription factors GATA1, FOG1, KLF1 and Ldb1 [14][15][16] ; the clustering of GAL genes or heat-shock genes requires transcription factor Gal4 or Hsf1 17,18 . Mutations of these factors will result in simultaneous loss of chromosomal interactions and gene expression, preventing us from elucidating the relation between them.…”
mentioning
confidence: 99%
“…The alteration of chromatin spatial structure, e.g, the genome compartments (Lieberman-Aiden et al, 2009b), the topological associated domains (TAD) (Dixon et al, 2012), and chromatin loops (Rao et al, 2014), has been suggested underling the transcriptional responses to HS in multiple species. In yeast, up-regulated HSP genes undergo dynamic alteration in their 3D genome structure (Chowdhary et al, 2017;Chowdhary et al, 2019). In Drosophila, HS induces relocalization of architectural proteins from TAD borders to inside TADs, and causes a dramatic rearrangement in the 3D organization of chromatin .…”
Section: Introductionmentioning
confidence: 99%